Pengaruh Dividend Payout Ratio dan Return on Assets Terhadap Harga Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) - Fadianti, Nurhas; Anwar Ramli; Nurman; Anwar; Annisa Paramaswary Aslam (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This research aims to determine the effect of Dividend Payout Ratio and Return on Assets on share prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The research sample used 5 companies using purposive sampling. The research method used is quantitative descriptive using multiple linear regression analysis and statistical hypothesis testing, partial tests and simultaneous tests using the SPSS version 24 program. The results of the research show that the Dividend Payout Ratio partially influences stock prices. All independent variables simultaneously influence the dependent variable. Simultaneously, there is a significant influence of DPR and ROA on share prices. In the test results, the coefficient of determination for Dividend Payout Ratio and Return on Assets was able to explain and contribute to share prices of 90.4%, while the remaining 9.6% was influenced by other variables.